CHURCH AND AFRICAN DESCENT IN THE CORREGIMIENTO OF ARICA. MORE SHADOWS THAN LIGHTS IN THE PLAN OF GOD AND MEN. DOCuMENTARY RECORDS EIGHTEENTH CENTURY. - Briones Valentín, Viviana (Revista de Historia Social y de las Mentalidades, 2024)
The slave population or free afro descendant  of Corregimiento of Arica was the subject  of an evangelization, the same as in the rest  of the Virreinato of Peru, according to the  needs of the slave system. A church overcame  for the economic expectations and exceeded  by the demands of reproducing a christian  moral of political and social effects failed or  didn’t know how to materialize his evangelist  vocation and Christian care required by this  type of population. More shadows trying to  portray this assistance or spiritual care that has  say for the documents presented in this article  corresponding to the 18th century, slaves or free  afro descendant were asking to all lights
Keywords: Slavery; Afro descendant; Corregi - miento of Arica; Colonial church; Evangelization; 18°th century